Establishment and Stability of the Murine Oral Microbiome. (June 2020) - Abusleme, L.; O'Gorman, H.; Dutzan, N.; Greenwell-Wild, T.; Moutsopoulos, N.M.
Commensal microbiomes exert critical functions at barrier sites. In particular, establishment of the commensal microbiome after birth dictates immune functionality and tissue homeostasis at mucosal surfaces. To investigate the establishment and stability of the oral mucosal microbiome in mice, we evaluated oral microbiome communities shortly after birth, through adulthood, and up to 1 y of life in a controlled manner, using sequential oral samples from the same mice over time. We further evaluated transmissibility of oral microbiomes from parents and during cohousing experiments and evaluated susceptibility to oral inflammatory disease in mice harboring distinct microbiomes. Our work reveals basic principles in the establishment and stability of a health-associated oral microbiome after birth and provides insights that may be important for host-microbiome experimentation in animal models.